Operações SAAL Porto — valor patrimonial e proposta de salvaguarda - Fernandes, João Luís da Mota Torres (CEM – Cultura, Espaço & Memória, 2021)
The present study aims to explicit the various positive heritage values inherent to the dwellings built in the city of Oporto as part of the operations undertook by the Service of Local Ambulatory Support (SAAL). Acknowledging these structures as testimony of a defining moment for the establishment of national identity – post 25th April 1974 –the appeal and validity of the safekeeping of these architectures will be grounded on the analysis of other case studies, relevant to the appreciation of Social Housing as a strong contribute towards the enrichment of national culture, finalizing with a presentation of heritage management methodologies applicable to the case in question.